Conflict mapping in spermonde archipelago: a case study of Pala, Laiya, Balang Lompo, Langkadea, and Barrang Caddi islands in Indonesia - Seniwati; Pujiyono; Arfin Sudirman; Munif Arif Ranti (Cogent Social Sciences, 2025)
This research aims to identify security threats and government policies in managing security tensions in the Spermonde Archipelago which includes Pala, Laiya, Balang Lompo, Langkadea and Barrang Caddi Islands. The study gap lies in the need for more literature that discusses small islands in the Spermonde Archipelago, focusing on security tension management. Various parties and stakeholders, including fishermen and women groups, collaborated through international cooperation to manage security tension on small islands, and data were collected from this innovative approach. The results showed that security threats in the Spermonde Archipelago are related to four conflict patterns which include the use of illegal fishing gear, conflict among horizontal groups, unidentified travelers, and lack of skills in processing sea products. Among the five islands, two islands, namely Balang Lompo and Barrang Caddi, utilized marine products at the international level through collaboration. Furthermore, the two islands empower women’s groups to process marine products into products ready for export. In conclusion, collaboration at the international level and community empowerment are two critical factors in managing security tensions on small islands.